Expressivist Semantics - Mendonça, Wilson (Veritas (Porto Alegre), 2016)
The semantic program of expressivism arose as an attempt to vindicate the noncognitivist view of ethical discourse, however it was soon generalized to cover normative language in general. It promises to develop a global alternative to the classical approach of truth-conditional semantics: a nonfactualist, pragmatics-based theory of linguistic meaning. Expressivists view the content of normative sentences as determined by their primary use, which is nondescriptive. Standard versions of expressivist semantics proceed by systematically assigning to normative sentences the mental attitudes they conventionally express. They assume that if simple sentences express attitudes, then applying to these sentences the compounding devices of the connectives of propositional logic or variable binding results in complex sentences which also express an attitude. The bulk of the paper assesses influent attempts to develop the expressivist program, thereby focusing on the vehemently debated “negation problem for expressivism.” Some very recently proposed approaches, which are based on the rejection of standard expressivists main assumption, are then considered in some detail. Although a definitive assessment of these novel approaches as satisfactory explanations of normative language cannot yet be reached, the paper claims that there is ground for optimism.